This study examines the usage behavior of Shopee PayLater from the perspective of Maqasid Shariah in Sinjai Regency - Rahmawati; Muslimin Kara; Sumarlin; Jamaluddin Majid; Muhamatsakree Manyunu (Universitas Muhammadiyah Makassar, 2026)
This study investigates the usage behavior of Shopee PayLater within the framework of Maqasid Shariah in Sinjai Regency, Indonesia. The research aims to explore user behavior patterns, identify the underlying motivations for adopting this digital credit service, and evaluate its alignment with Islamic ethical principles. A qualitative approach within a critical paradigm was employed, involving purposively selected participants, including lecturers, religious leaders, students, and community members who actively use Shopee PayLater. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using the Miles and Huberman interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that Shopee PayLater usage is predominantly influenced by convenience, urgent financial needs, and social factors, leading to two primary patterns: consumptive and productive use. While the service provides benefits such as facilitating access to essential goods and supporting small-scale economic activities, it also encourages impulsive consumption and poses risks of financial distress. From the Maqasid Shariah perspective, the practice partially aligns with the objectives of preserving life and wealth (hifz al-nafs and hifz al-mal), but may contradict the protection of religion and intellect (hifz al-din and hifz al-‘aql) due to elements of riba, excessive consumption, and weak financial discipline. This study contributes to the development of Islamic fintech discourse by integrating behavioral analysis with Maqasid Shariah and offers practical insights for policymakers, fintech providers, and Muslim consumers to promote ethically responsible digital financial practices.